Rotavirus-associated hospitalization and emergency department costs and rotavirus vaccine program impact() - Kilgore, April (Vaccine, 2013)
OBJECTIVES: To determine the medical costs of laboratory-confirmed rotavirus hospitalizations and emergency department (ED) visits and estimate the economic impact of the rotavirus vaccine program. PATIENTS AND METHODS: During 4 rotavirus seasons (2006–2009), children <3 years of age hospitalized or seen in the ED with laboratory-confirmed rotavirus were identified through active population-based rotavirus surveillance in three US counties. Medical costs were obtained from hospital and physician billing data, and factors associated with increased costs were examined. Annual national costs were estimated using rotavirus hospitalization and ED visit rates and medical costs for rotavirus hospitalizations and ED visits from our surveillance program for pre- (2006–2007) and post-vaccine (2008–2009) time periods. RESULTS: Pre-vaccine, for hospitalizations, the median medical cost per child was $3581, the rotavirus hospitalization rate was 22.1/10,000, with an estimated annual national cost of $91 million. Post-vaccine, the median medical cost was $4304, the hospitalization rate was 6.3/10,000 and the estimated annual national cost was $31 million. Increased costs were associated with study site, age <3 months, underlying medical conditions and an atypical acute gastroenteritis presentation. For ED visits, the pre-vaccine median medical cost per child was $574, the ED visit rate was 291/10,000 resulting in an estimated annual national cost of $192 million. Post-vaccine, the median medical cost was $794, the ED visit rate was 71/10,000 with an estimated annual national cost of $65 million. CONCLUSIONS: After implementation of rotavirus immunization, the total annual medical costs decreased from $283 million to $96 million, an annual reduction of $187 million